Nickel and Chromium Deposition by Hot Target Magnetron Sputtering; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Sidelev D. V. Dmitry Vladimirovich; Bleykher (Bleicher) G. A. Galina Alekseevna; Grudinin V. A. Vladislav Alekseevich; Krivobokov V. P. Valery Pavlovich (Ion-Assisted Coating Deposition. Oral Presentation, 2019)
Заглавие с экрана